Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Discover precise answers to your questions from a wide range of experts on our user-friendly Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
In this type of equation you could use different methods. But I choose to do Quadratic Method.
a= 3, b= 8, and c= 4.
X= -(8)+_SQUARE ROOT (8)^2-4(3)(4)/2(3)
X= -8+_SQUARE ROOT16/6 Square Root of 16 is 4
X= -8+_4/6
X= -8+4/6= -4/6= -2/3.
X= -8-4/6= -12/6= -2.
Answer is: -2/3 and -2.
3x² + 8x + 4
First, i divide the equation into two parenthesis, so that the first parts of both multiply to make the first term, 3x². 3x * x = 3x²
(3x + )(x + )
Then I find two numbers that multiply to make 4, which are 1 and 4, or 2 and 2.
Our options are:
(3x + 1)(x + 4)
(3x + 4)(x + 1)
(3x + 2)(3x +2)
To figure out which one to use, I'm just going to FOIL them all.
(3x + 1)(x + 4) = 3x² + 1x + 12x + 4 = 3x² + 13x + 4
(3x + 4)(x + 1) = 3x² + 4x + 3x + 4 = 3x² + 7x + 4
(3x + 2)(x +2) = 3x² + 2x + 6x + 4 = 3x² + 8x + 4
The factored form is:
(3x + 2)(x + 2)
To solve for the roots ( where the graph crosses the x axis, where y = 0) we set the equation equal to 0:
(3x + 2)(x + 2) = 0
The zero product property says that anything times 0 is 0, so we set each individual part equal to 0 and solve for the two roots.
3x + 2 = 0
3x = -2
x = -2/3
x + 2 = 0
x = -2
First, i divide the equation into two parenthesis, so that the first parts of both multiply to make the first term, 3x². 3x * x = 3x²
(3x + )(x + )
Then I find two numbers that multiply to make 4, which are 1 and 4, or 2 and 2.
Our options are:
(3x + 1)(x + 4)
(3x + 4)(x + 1)
(3x + 2)(3x +2)
To figure out which one to use, I'm just going to FOIL them all.
(3x + 1)(x + 4) = 3x² + 1x + 12x + 4 = 3x² + 13x + 4
(3x + 4)(x + 1) = 3x² + 4x + 3x + 4 = 3x² + 7x + 4
(3x + 2)(x +2) = 3x² + 2x + 6x + 4 = 3x² + 8x + 4
The factored form is:
(3x + 2)(x + 2)
To solve for the roots ( where the graph crosses the x axis, where y = 0) we set the equation equal to 0:
(3x + 2)(x + 2) = 0
The zero product property says that anything times 0 is 0, so we set each individual part equal to 0 and solve for the two roots.
3x + 2 = 0
3x = -2
x = -2/3
x + 2 = 0
x = -2
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.